Training on the Implementation of ISO 31000 Risk Management for Blitar City Food Business Association - Utama, Adiguna; Latifah, Nunuk; Kurniawan, Hindra; Normawati, Rani Arifah; Wardani, Shanti Ike; Widayani, Anna; Rachmawati, Ika (Outline Publisher, 2025)
The food micro, small, and medium enterprises in Blitar face significant challenges in managing various business risks, including financial, operational, and strategic risks, which often hinder business continuity and growth. This study aims to enhance the risk management capabilities of food business actors in Blitar through a structured training program based on the international ISO 31000 standard. The training was delivered using lectures, discussions, and case studies, and its effectiveness was evaluated using the Kirkpatrick Level 2 method by comparing participants’ understanding before and after the training. Data were collected through pre-test and post-test questionnaires covering key aspects of risk management knowledge and practical application. The results demonstrate a substantial improvement in participants’ comprehension, with the average score increasing from 1.85 before the training to 3.65 after the training. The most significant gains were observed in the practical use of risk matrices and the identification of major risk categories, while the smallest improvement was found in the area of financial record separation, which already had a high baseline understanding. These findings indicate that the training was effective in increasing both conceptual and practical understanding of risk management among food business actors in Blitar. It is concluded that systematic risk management training based on international standards can significantly strengthen the resilience and sustainability of micro, small, and medium enterprises in the local food sector.